Transfection of Antisense Oligonucleotides Mediated by Cationic Vesicles Based on Non-Ionic Surfactant and Polycations Bearing Quaternary Ammonium Moieties - Mayr, Judith (Int J Mol Sci, 2017)
Three different ionene polymers with varying quaternary ammonium moieties were used as a proof of concept for the formulation of antisense oligonucleotides, which are capable of inhibiting Renilla luciferase messenger ribonucleic acid (mRNA). Cationic vesicles, consisting of cationic polymer, antisense oligonucleotide (Luc) and non-ionic surfactant polysorbate 80, were investigated regarding their ζ potential, cytotoxicity and transfection efficiency. Deoxyribonucleic acid- (DNA) forming complexes in the presence of cationic vesicles were also investigated in terms of small-angle X-ray scattering (SAXS). The studied cationic vesicles showed very little, if any, toxicity against HeLa cells. Transfection abilities proved to vary strongly depending on the present quaternary ammonium moiety.